Using sport science to improve coaching: A case study of Felisha Johnson`s Road to Rio - Judge, L. W.; Cheetham, P. J.; Fox, B.; Schoeff, M. A.; Wang, H.; Momper, M.; Dickin, D. C. (International Journal of Sports Science & Coaching, 2021)
During a shot put, there are different finite variables that can be controlled by the thrower, including release angle, release height, release direction, and release velocity. Previous studies have determined thresholds of release velocity necessary for achieving certain distances, and this case study sought to expand upon that concept. Conclusions from key biomechanical data can make a significant difference in the performance of athletes in the shot put if properly understood by coaches. By utilizing this scientific approach to the shot put event, the throws coach will be able to determine more accurate adjustments and devise training stimuli to better accommodate the athlete. In this case study, researchers and the coach attempted to bridge the gap in the approach to teaching and coaching the glide shot put by using a physics-based equation regarding projectile motion in tandem with biomechanical analyses. The use of immediate feedback via video analysis was an essential part the coaching and teaching system. The athlete`s release angles decreased, and her maximum release velocities increased from 12.5 m/s in 2015 to 13.1 m/s in 2016. This USATF coaching education shot put project is an example in which the cooperation between sport science and coaching helped to produce an Olympic berth (19.24 m) by Felisha Johnson in the women`s shot put in 2016.